Burns Wound-Healing Activity in Male White Rats of Matoa Stem Bark (Pometia pinnata) Ethanolic Extract - Lilianturi, Fresi; Fajriyah, Shofiatul Fajriyah; Shoviantari, Fenita (Universitas Islam Negeri Alauddin Makassar, 2023)
Introduction: Burns are a global public health problem. The activity of herbal products in stimulating burn wound healing is supported by many animal studies and few clinical trials. The people of Papua New Guinea use the chewed bark of the matoa tree to heal burns. Matoa's stem bark contains flavonoids, terpenoids and tannins that promote wound healing. These compounds have antimicrobial, antioxidant and wound healing properties. They increase blood clotting, fight infection and accelerate wound healing. Aims: The aim of this research was to determine whether ethanol extract of Matoa stem bark has anti-burn activity against male white rats of the Sprague Dawley strain. Method: In this study, a method was used to measure the area of burn wound in 5 treatment groups for 14 days. Group I were treated with the MEBO ointment (the positive control group); Group II with vaseline flavum (the negative control); Group III was given Matoa bark extract ointment at a concentration of 10%; group IV at a concentration of 20%, while group V at a concentration of 30%. Result: Qualitative analysis of chemical compounds shows that the ethanolic extract of Matoa stem bark contains flavonoids, triterpenoid tannins, and saponins. Ethanol extract of matoa bark 20% and 30% had burn wound healing activity in male Sprague-Dawley white rats. Activity was significantly different from negative control and not significantly different from positive control. Conclusion: A 20% and 30% ethanolic extract of the stem bark Matoa is considered a topical agent for use in treating burns wound.